2018
DOI: 10.4097/kjae.2018.71.1.48
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative factors associated with pressure ulcer development after major surgery

Abstract: BackgroundPostoperative pressure ulcers are important indicators of perioperative care quality, and are serious and expensive complications during critical care. This study aimed to identify perioperative risk factors for postoperative pressure ulcers.MethodsThis retrospective case-control study evaluated 2,498 patients who underwent major surgery. Forty-three patients developed postoperative pressure ulcers and were matched to 86 control patients based on age, sex, surgery, and comorbidities.ResultsThe pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 26 publications
(33 reference statements)
4
45
0
7
Order By: Relevance
“…Our study found low BMI and low preoperative Braden score to be significant predictors of HAPU, which is consistent with other similar studies . However, there are also studies that identified the postoperative Braden score as a significant predictor of HAPU . Therefore, we performed an additional secondary analysis on the postoperative Braden score and found that it was also statistically significant in our univariate analysis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study found low BMI and low preoperative Braden score to be significant predictors of HAPU, which is consistent with other similar studies . However, there are also studies that identified the postoperative Braden score as a significant predictor of HAPU . Therefore, we performed an additional secondary analysis on the postoperative Braden score and found that it was also statistically significant in our univariate analysis.…”
Section: Discussionsupporting
confidence: 91%
“…7,12,21,24 However, there are also studies that identified the postoperative Braden score as a significant predictor of HAPU. 33,34,41 Therefore, we performed an additional secondary analysis on the postoperative Braden score and found that it was also statistically significant in our univariate analysis. However, we did not include it in our prediction model because we wanted to use variables that are available preoperatively to determine a patient's pressure ulcer risk.…”
Section: Resultsmentioning
confidence: 89%
“…Other studies report that the Braden Scale had no effect on determining the risk of perioperative pressure injury . Conversely, a 2018 study reported that higher Braden Scale scores upon admission were correlated with perioperative pressure injuries . The Braden Scale may not play a role in determining perioperative pressure injury risk because perioperative risk factors such as procedure duration and type, intraoperative blood pressure, and intraoperative vasopressor use cannot be assessed in the variables included in that scale.…”
Section: Discussionmentioning
confidence: 99%
“…17,37 Conversely, a 2018 study reported that higher Braden Scale scores upon admission were correlated with perioperative pressure injuries. 24 The Braden Scale may not play a role in determining perioperative pressure injury risk because perioperative risk factors such as procedure duration and type, intraoperative blood pressure, and intraoperative vasopressor use cannot be assessed in the variables included in that scale. The Braden Scale was developed based on risk factors relevant for patients receiving home care and may not be appropriate for assessing patients undergoing operative and other invasive procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation